From Cognition to Behavior: Associations of Workplace Health Culture and Workplace Health Promotion Performance With Personal Healthy Lifestyles - Chang, Yao-Tsung; Tsai, Feng-Jen; Yeh, Ching-Ying; Chen, Ruey-Yu (Frontiers in Public Health, 2021)
Introduction: The aim of this study was to explore associations of workplace health culture and workplace health promotion (WHP) performance with employees' healthy lifestyles and health statuses. Methods: In total, 27 enterprises and 1,732 participants were recruited for a cross-sectional designed survey. At the group level, Workplace Health Scorecard was used to measure WHP performance, and it was filled out by the WHP representative at each workplace. At the personal level, a personal questionnaire was used to measure workplace health culture, healthy lifestyles, and health statuses. A hierarchical linear model analysis was used to assess correlations between these variables. Results: Workplace health culture was significantly related to WHP performance, healthy lifestyles, and health statuses. In particular, the peer support domain was greatly related to healthy behaviors like physical activity (β = 0.596, p < 0.001), vegetable consumption (β = 0.291, p < 0.001) and fruit consumption (β = 0.285, p < 0.05), and it may illustrate the importance of establishing peer support to promote healthy behaviors. Conclusions: WHP performance was significantly related to workplace health culture especially health policies, health climate, and peer and supervisor support. Hence, building a good workplace health culture should be taken seriously, and more studies exploring associations of health culture and WHP performance with employees' health are needed.